Natural Compounds Regulate Glycolysis in Hypoxic Tumor Microenvironment. (22nd January 2015) - Gao, Jian-Li; Chen, Ying-Ge
Abstract : In the early twentieth century, Otto Heinrich Warburg described an elevated rate of glycolysis occurring in cancer cells, even in the presence of atmospheric oxygen (the Warburg effect). Recently it became a therapeutically interesting strategy and is considered as an emerging hallmark of cancer. Hypoxia inducible factor-1 (HIF-1) is one of the key transcription factors that play major roles in tumor glycolysis and could directly trigger Warburg effect. Thus, how to inhibit HIF-1-depended Warburg effect to assist the cancer therapy is becoming a hot issue in cancer research. In fact, HIF-1 upregulates the glucose transporters (GLUT) and induces the expression of glycolytic enzymes, such as hexokinase, pyruvate kinase, and lactate dehydrogenase. So small molecules of natural origin used as GLUT, hexokinase, or pyruvate kinase isoform M2 inhibitors could represent a major challenge in the field of cancer treatment. These compounds aim to suppress tumor hypoxia induced glycolysis process to suppress the cell energy metabolism or enhance the susceptibility of tumor cells to radio- and chemotherapy. In this review, we highlight the role of natural compounds in regulating tumor glycolysis, with a main focus on the glycolysis under hypoxic tumor microenvironment.